Probiotics improve renal function, glucose, lipids, inflammation and oxidative stress in diabetic kidney disease: a systematic review and meta-analysis - Dai, Yali; Quan, Jingjing; Xiong, Lianlian; Luo, Yanfang; Yi, Bin (Renal failure, 2022)
The role of probiotics in the management of diabetic kidney disease (DKD) has been shown. Several current trials are investigating the effect of probiotics, which are widely used to modulate biomarkers of renal function, glucose, lipids, inflammation and oxidative stress in patients with DKD. However, their findings are controversial. This study aimed to systematically evaluate the impact of probiotics on patients with DKD via meta-analysis. PubMed, The Cochrane Library, Web of Science, Scopus, Embase, China National Knowledge Infrastructure, Chinese Wanfang Database and Chinese VIP Database were searched for relevant studies from the establishment of these databases to September 2021. The pooled results evaluated the impact of probiotics on renal function, glucose, lipids, inflammation and oxidative stress indicators in patients with DKD. Additionally, subgroup analysis was performed based on intervention duration, probiotic dose and probiotic consumption patterns, respectively. Ten trials that included 552 participants were identified for analysis. Compared with the controls, probiotics significantly decreased serum creatinine (Scr) [WMD = −0.17 mg/dL; 95%CI = −0.29, −0.05; p = 0.004], blood urea nitrogen (BUN) [WMD = −1.36 mg/dL; 95%CI = −2.20, −0.52; p = 0.001], cystatin C (Cys C) [WMD = −29.50 ng/mL; 95%CI = −32.82, −26.18; p < 0.00001], urinary albumin/creatinine ratio (UACR) [WMD = −16.05 mg/g; 95%CI = −27.12, −4.99; p = 0.004] and natrium (Na) [WMD = −0.94 mmol/L; 95%CI = −1.82, −0.05; p = 0.04] in patients with DKD. Enhanced glycemic control was observed in patients with DKD receiving probiotics compared with controls, as demonstrated by reduced levels of fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), homeostasis model of assessment-estimated insulin resistance (HOMA-IR), and increased quantitative insulin sensitivity check index (QUICKI). Probiotics affected lipid metabolism parameters with decreasing triglycerides (TG), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) levels in patients with DKD. Probiotics could also could improve inflammation and oxidative stress by decreasing high-sensitivity C-reactive protein (hs-CRP), plasma malondialdehyde (MDA), total antioxidant capacity (TAC), glutathione (GSH) and nitric oxide (NO). Additionally, subgroup analysis showed that those who received multiple species probiotics had a statistically significant difference in BUN, FPG, HOMA-IR, high-density lipoprotein cholesterol (HDL-c), MDA, TAC, and NO. Meanwhile, Scr, LDL-c, HDL-c, MDA, and TAC were ameliorated when the intervention duration was more than eight weeks and BUN, FPG, HOMA-IR, and MDA were improved when the probiotic dose was greater than four billion CFU/day. Our analysis revealed that probiotics could delay the progression of renal function injury, improve glucose and lipid metabolism, and reduce inflammation and oxidative stress in patients with DKD. Subgroup analysis showed that intervention duration, probiotic dose and probiotic consumption patterns had an effect of probiotics on outcomes.